METHODOLOGICAL FOUNDATIONS OF WORKING WITH CHILDREN WITH SPECIAL NEEDS (Web of Teachers: Inderscience Research, 2025)
This article discusses the organization of the inclusive education process and its effectiveness. At the same time, it is described how the practical application of methods used in inclusive education can help develop students' social and cognitive skills.